Gazdasági Társaságok könyvvezetési pénznemének számviteli törvény szerinti szabályozása, Forintról Euró alapú könyvvezetésre való áttérés folyamatának bemutatása egy adott nagyvállalati példán keresztül - Horváth Zsuzsanna (2019)
In Hungary there is a growth the number of companies that pursue international commercial activities in foreign currencies. (espescially in Euro) These companies are exposed to a currency risk depending on amount of the forex trading activities. The exchange rate risk can have serious impact for the activites and the result of these companies, espesscially if they has a significant presence in foreign markets. One effective way to reduce the above mentioned problems resulting from the exchange rate risk arising from volatility of the exchange rates is to change the base currancy of the General Ledger so called Euro changeover. Of course this base currency changeover is only the apropriate solution for companies which has their main income and costs are in the choosen currecny and besides this another outcome is that the annual planning and results analises will be significantly more predictable and simplier. This kind of based currency changeover should be implemented only on the balance sheet date which requires a prudent and well organized preparational work. My diploma theses is about such a project in a daughter maunfacturing company of an international corporate group, where I have investigated the Euro changeover based on the legal background, preparational tasks, steps of the implementation and the conversion methodology, respectively the challenges, dangers and risks, which has raised during the implementation process.